2016
DOI: 10.1248/bpb.b16-00025
|View full text |Cite
|
Sign up to set email alerts
|

Carbonyl Compounds in the Gas Phase of Cigarette Mainstream Smoke and Their Pharmacological Properties

Abstract: Cigarette mainstream smoke is composed of gas and tar phases and contains >4000 chemical constituents, including nicotine and tar. The substances in the gas phase but not in the tar phase can pass through the airway epithelial barrier, enter the systemic circulation via the pulmonary circulation, and increase systemic oxidative damage, leading to the development of cigarette smoking-related diseases such as atherosclerosis. Recently, we identified some stable carbonyl compounds, including acrolein (ACR) and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 40 publications
1
39
0
Order By: Relevance
“…The exposure of mice to cigarette smoke is an important way to investigate the role of oxidative stress in AMD because cigarette smoking is the most significant modifiable risk factor in AMD [47,54]. Cigarette smoke contains several potent oxidants, including hydroquinone (HQ), nicotine, and cadmium [55,56]. This animal model has helped to understand possible molecular events that might lead to AMD.…”
Section: Cigarette Smokementioning
confidence: 99%
“…The exposure of mice to cigarette smoke is an important way to investigate the role of oxidative stress in AMD because cigarette smoking is the most significant modifiable risk factor in AMD [47,54]. Cigarette smoke contains several potent oxidants, including hydroquinone (HQ), nicotine, and cadmium [55,56]. This animal model has helped to understand possible molecular events that might lead to AMD.…”
Section: Cigarette Smokementioning
confidence: 99%
“…Most of the effects of cigarette on human body are due to toxic components in the cigarette smoke. Cigarette smoke consists of two phases; tar phase and gas phase . Both phases are rich in reactive oxygen and nitrogen species which were strongly related to apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Carbonyls such as acrolein have been linked to the induction of cellular oxidative stress 24 and it has been reported that carbonyls are captured in AqE. 23,[25][26][27][28] Furthermore, the ratio of carbonyl components of AqE are similar to that observed in cigarette smoke, although the absolute levels were lower. 29 The antioxidant status of NCI-H292 lung epithelial cells was assessed using the GSH-GloÔ assay to measure changes in the level of the reduced form of the antioxidant glutathione.…”
Section: Figmentioning
confidence: 79%
“…[3][4][5][20][21][22] Cigarette smoke has an abundance of free radicals, with the vapor phase tending to contain shortlived species that exert their damaging effects locally, whereas the longer-lived species tend to act systemically and are found in the particulate phase. 23 We compared oxidative stress levels indirectly by measuring both ROS pro-duction and the antioxidant status of lung epithelial cells in response to smoke from RTP or CC cigarettes. Exposure to PM induced a dose-dependent increase in ROS production, however no differences were observed between cigarettes.…”
Section: Figmentioning
confidence: 99%